Leadership Influence Andorganizational Culture on the Performance of PT Heksa Artha Bangkalan Employees with the Working Environment as Mediator - Eric Hernawan; Wahyuddin Latunreng; Antoni Ludfi Arifin (Budapest International Research and Critics University, 2022)
The independent variable of the work environment in this study was used as a mediator to determine the indirect effect of leadership and organizational culture on the performance of employees of PT. Heksa Artha Sakti Bangkalan. This indirect effect can be determined by determining the direct influence of leadership, culture and work environment partially on the performance of employees of PT. Heksa Artha Sakti Bangkalan. Coupled with the direct partial influence of leadership and culture on the work environment. This study processed the questionnaire data as many as 50 respondents from the population of 85 employees of PT. Heksa Artha Sakti Bangkalan. The calculation of simple linear regression and multiple linear regression was determined after the research data met the validity, reliability, normality, multicollinearity and heteroscedasticity tests. The significance test for the simple regression was carried out by t-test, by comparing tcount and ttable. The simple regression equation is significant and positive if tcount > ttable. Meanwhile, the significance test for multiple regression was carried out using the F-test, by comparing Fcount with Ftable. The multiple regression equation is significant and positive if Fcount > Ftable. The results obtained from this study, all effects, both direct and indirect, are significant and positive. The influence in percent (%) for leadership, organizational culture and work environment separately on the performance of employees of PT. Heksa Artha Sakti Bangkalan was 47.4%, 33.1%. and 29.8%. The direct influence of leadership and organizational culture on the work environment are 35.8% and 33.9%, while the influence of leadership, organizational culture and work environment simultaneously on the performance of employees of PT. Heksa Artha Sakti Bangkalan is 47.8%